IMPORTANCE OF THE INTERNET RESOURCES IN LEARNING ENGLISH - Raimov Olimjon; Sevara Muradova (Galaxy International Interdisciplinary Research Journal, 2023)
This article aims to outline numerous useful Internet Resources such as websites for foreign language learners. In the article we will introduce them in detail and give important input about them. Actually, those sites are very handy for second language acquisition. In the following parts of the article you may get some information about the resources. In fact, these websites are proven and they are available to utilize.